2022
DOI: 10.3389/fspas.2022.1020635
|View full text |Cite
|
Sign up to set email alerts
|

The reactivity of pyridine in cold interstellar environments: The reaction of pyridine with the CN radical

Abstract: The recent detection of cyclic species in cold interstellar environments is an exciting discovery with yet many unknowns to be solved. Among them, the presence of aromatic heterocycles in space would act as an indirect evidence of the presence of precursors of nucleotides. The seeming absence of these species in the observations poses a fascinating conundrum that can be tackled with computational insights. Whilst many arguments can be given to explain the absence of heterocycles in space, one of the possible s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It is questionable if pyridine is readily available on ice grains, as this rather complex molecule was never detected in the interstellar medium. [117][118][119][120] Anyway, there needs to be an explanation as to why Smith et al [12] found picolin-isomers in dominating amounts in meteorites, and Oba et al [13,14] did not. They might be inherited from ice grain processes and either very heterogeneously distributed in the same parent body, or the CM2 chondrites originate from several different bodies with different chemical histories.…”
Section: Comparison To Measured Abundances In Meteorites and Asteroid...mentioning
confidence: 99%
“…It is questionable if pyridine is readily available on ice grains, as this rather complex molecule was never detected in the interstellar medium. [117][118][119][120] Anyway, there needs to be an explanation as to why Smith et al [12] found picolin-isomers in dominating amounts in meteorites, and Oba et al [13,14] did not. They might be inherited from ice grain processes and either very heterogeneously distributed in the same parent body, or the CM2 chondrites originate from several different bodies with different chemical histories.…”
Section: Comparison To Measured Abundances In Meteorites and Asteroid...mentioning
confidence: 99%
“…However, no respective chromatography‐mass spectroscopy data were provided to support these findings. It is questionable if pyridine is readily available on ice grains, as this rather complex molecule was never detected in the interstellar medium [117–120] …”
Section: Resultsmentioning
confidence: 99%
“…It is questionable if pyridine is readily available on ice grains, as this rather complex molecule was never detected in the interstellar medium. [117][118][119][120] Anyway, there needs to be an explanation as to why Smith et al [12] found picolin-isomers in dominating amounts in meteorites, and Oba et al [13,14] did not. They might be inherited from ice grain processes and either very heterogeneously distributed in the same parent body, or the CM2 chondrites originate from several different bodies with different chemical histories.…”
Section: Comparison To Measured Abundances In Meteorites and Asteroid...mentioning
confidence: 99%